Recent advances in plant biotechnology and genetic engineering for production of secondary metabolites - Sheludko, Y.V. (Цитология и генетика, 2010)
For a long time people are using plants not only as crop cultures but also for obtaining of various chemicals. Currently plants remain one of the most important and essential sources of biologically active compounds in spite of progress in chemical or microbial synthesis. In our review we compare potentials and perspectives of modern genetic engineering approaches for pharmaceutical biotechnology and give examples of actual biotechnological systems used for production of several promising natural compounds: artemisinin, paclitaxel and scopolamine. З давніх часів люди використовували рослини не тільки як харчові культури, але і для отримання різноманітних хімічних сполук. Незважаючи на сучасний розвиток методів хімічного синтезу й мікробіологічних біотехнологій, рослини залишаються найважливішим і незамінним джерелом біологічно активних речовин. В огляді ми зіставили можливості й перспективи використання сучасних методів генетичної інженерії в фармацевтичній біотехнології і навели приклади сучасних біотехнологічних систем, які застосовують для одержання деяких цінних натуральних продуктів – артемізініна, паклітаксела і скополаміна. С давних времен растения использовались людьми не только как пищевые культуры, но и для получения разнообразных химических соединений. Несмотря на современное развитие химических методов синтеза и микробиологических биотехнологий, растения остаются важнейшим и незаменимым источником биологически активных веществ. В обзоре мы сопоставили возможности и перспективы использования современных методов генетической инженерии в фармацевтической биотехнологии и привели примеры новейших систем, используемых для получения некоторых ценных натуральных продуктов – артемизинина, паклитаксела и скополамина.